72 Mental outcome of workers 12 months after occupational injury. (11th October 2013) - Shiao, S C; Lin; Guo; Liao; Guo; Kuo; Hu; Hsu
Abstract : Objectives: Workers hospitalised after occupational injury are at risk for psychiatric disorders. This study aimed to examine prevalence rates of both post-traumatic stress disorder (PTSD) and major depression at 12 months in workers experiencing different types of occupational injury in Taiwan. Methods: Workers sustaining occupational injury and hospitalised for 3 days or longer and received hospitalisation benefits from the Labour Insurance program were recruited in this study. A two-staged survey study was conducted. A self-reported questionnaire including the Brief Symptom Rating Scale (BSRS-50) and Post-traumatic Symptom Checklist (PTSC) was sent to workers at 12 months after injury. Those who scored high and suspected to have mental conditions were recruited for the second stage phone interview with a psychiatrist using the Mini-international Neuropsychiatric Interview (MINI). Results: A total of 1233 workers completed the questionnaire. Among them, 167 (13.5%) scored high in either BSRS or PTSC and were invited for the MINI interview. A total of 106 (63.5%) completed the phone interview. The estimated rates of PTSD, partial PTSD (PPTSD), major depression, comorbid PTSD/PPTSD and major depression, and either PTSD/PPTSD or major depression were 3.4%, 1.8%, 2.0%, 2.0%, and 5.2%, respectively. The risk factors for high scores in either BSRS or PTSC were gender, education level, marriage status, loss of consciousness after occupational injury, injury affecting physical appearance, occupational injury experience before this event, traumatic life events before and after this injury, length of hospital stay, self-rated injury severity, and the worker's proportion of income contribution to the family. Conclusions: Occupational injury can cause long-term mental condition in the workers. The identified risk factors in this study may provide valuable information for developing preventive strategies.